1996
DOI: 10.1093/sjaf/20.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Ice Damage in Thinned and Nonthinned Loblolly Pine Plantations Infected with Fusiform Rust

Abstract: Portions of two loblolly pine (Pinus taeda L.) plantations in central Georgia were thinned in 1982 to remove trees with severe fusiform rust infections on the main stem. In January 1983, a widespread ice storm damaged both plantations. Stem breakage and storm-related mortality were greater in thinned than in nonthinned portions of the plantations. There was a weak association between the occurrence of stem breakage and location of rust infections. Tree-ring chronologies show that trees with the greatest potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“… Rubin and Manion [2001] suggested the relationship between damage and diameter might depend on the tree species. Belanger et al [1996] found no difference in damage to loblolly pines ( Pinus taeda L.) of different size classes (DBH) following an ice storm. Ryall and Smith [2005] observed that large diameter trees were less damaged by ice accumulation than small diameter trees.…”
Section: Discussionmentioning
confidence: 96%
“… Rubin and Manion [2001] suggested the relationship between damage and diameter might depend on the tree species. Belanger et al [1996] found no difference in damage to loblolly pines ( Pinus taeda L.) of different size classes (DBH) following an ice storm. Ryall and Smith [2005] observed that large diameter trees were less damaged by ice accumulation than small diameter trees.…”
Section: Discussionmentioning
confidence: 96%
“…Wiley and Zeide (1991) observed a reduction in diameter growth of Pinus taeda for 8 years after the 1974 ice storm in southeast Arkansas that caused severe crown damage, bending and breakage of stems; the following 6 years, however, showed similar or increased diameter growth of broken trees relative to undamaged trees (see also Bragg & Shelton, 2010). Belanger et al (1996) also reported a lack of recovery in diameter growth of Pinus taeda with severe crown damage for a 5 year period following the 1983 storm in central Georgia. Similar effects may have resulted in reduced radial growth of Pinus taeda observed in our study for up to 4 years following the extreme storms.…”
Section: Influence Of Climate and Extreme Storm Events On Tree Ring Gmentioning
confidence: 99%
“…For those trees that suffer damage from ice storms, the growth of individual trees following ice storm damage is strongly dependent on the total crown loss (Belanger et al, 1996). In an 18-20 year old loblolly pine plantation, 28% of those critically injured (greater than 70% crown loss) died within the first growing season following a severe ice storm, while only 2% of less damaged individuals died (Bragg et al, 2002).…”
Section: Morphological Differences and Ice Storm Responsementioning
confidence: 99%
“…Shepard (1975) reported that individuals with smaller diameters were more likely to bend or be uprooted than individuals with larger diameters, which were more susceptible to snapping. Previous studies have reported that stem breakage of loblolly pines is most susceptible when DBH is between 12 -25 cm (Downs, 1943;Wiley and Zeide, 1991;Amateis and Burkhart, 1996;Belanger et al, 1996;Zeide and Sharer, 2001;Bragg et al, 2003;Bragg et al, 2004), and stem breakage below the live crown is fatal to southern pines (Abel, 1948). Our results were in general agreement with these previous findings, with the diameter range for snapped bole occurring at larger diameters (12 to 22 cm) than bent bole.…”
Section: Morphological Differences and Ice Storm Responsementioning
confidence: 99%
See 1 more Smart Citation